Semiotic Analysis of John Fiske on Terrorism in The Film 13 BOM di Jakarta - Laila Jannatul Fajri; Amelia Puspita; Mohammad Ali Wafa (CV. Publikasi Indonesia, 2025)
13 Bom di Jakarta is an Indonesian movie inspired by Indodax's true story related to terrorism cases in 2015. This movie tells the story of a bomb terror case in Jakarta. In this movie, the Indonesian Counter Terrorism Agency receives a threat from a person who is considered a terrorist. The person said there were 13 bombs that they had spread throughout the city of Jakarta and the person asked for 100 Bitcoin through Indodax or they would explode the bomb every eight hours. This research aims to identify signs related to terrorism in the movie